Prediction Model of Human Immunodeficiency Virus Status at Abdoel Wahab Sjahranie Hospital, Samarinda - Asari, Sendila Ernesy; Susanti, Rahmi; AB, Ismail; Pakki, Irfansyah Baharuddin; Anggraini, Ike (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: HIV is a serious global health problem that requires immediate attention due to its increasing prevalence. Indonesia having one of the highest numbers of cases, while East Kalimantan was one of the provinces with a high number of cases. The availability of HIV testing and counseling services at RSUD Abdoel Wahab Sjahranie enabled the researchers to analyze factors that influence HIV occurrence. This study aimed to find a prediction model for HIV status.Methods: This cross-sectional study used secondary data from 7,589 individuals from the Voluntary Counseling and Testing (VCT) Clinic of RSUD Abdoel Wahab Sjahranie from June to December 2023. Data were collected from January to March 2024. The data were analysed using the logistic regression method.Results: It was shown that age, injection drug use, and types of sexual behavior were significantly associated to HIV status. The obtained binary logistic regression model is: HIV status = -4.729-0,032 (age) + 6,862 (injection drug use) + 6,173 (type of sexual behavior). This model could explain 53.8 percent of the variation in HIV status based on the independent variables, with injection drug use as the dominant variable. Injection drug use and risky sexual behavior were significant factors of HIV status.Conclusion: Injection drug users were at greater risk of HIV infection, with the highest odds ratio, followed by persons with risky sexual behavior. Further intervention efforts through expanding service coverage and diagnostic testing for key populations to prevent HIV transmission is needed